Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete - Chatzaki, Maria; Arnedo, Miquel A. (Zootaxa, 2006)
Here we review the taxonomy of the epigean species of the spider subfamily Harpacteinae (Araneae, Dysderidade) on Crete. Along with the endemic cave-dwelling genus Minotauria, this subfamily is represented on this island by the genera Harpactea and Stalagtia, the last of which is reported for the first time. We describe and illustrate the previously unknown females of Harpacteacressa Brignoli, 1984 and Harpactea coccifera Brignoli, 1984. Furthermore, a new species, Stalagtia thaleriana n. sp., is described and a critical appraisal and a re-delimitation of the current definition of the genus Stalagtia is provided. An identification key, some notes on the ecology (habitat preferences, activity periods) and the distribution of these species on Crete are also given.